Atomically resolved chemical ordering at the nm-thick TiO precipitate/matrix interface in V-4Ti-4Cr alloy. (1st January 2017) - Impagnatiello, A.; Hernandez-Maldonado, D.; Bertali, G.; Prestat, E.; Kepaptsoglou, D.; Ramasse, Q.; Haigh, S.J.; Jimenez-Melero, E.
Abstract: We have used advanced analytical electron microscopy to characterise the local structure and chemistry at the interface between nm-thick TiO precipitates and the V-based matrix in a V-4Ti-4Cr alloy. Our results reveal the presence of an intergrowth between the fcc TiO and bcc vanadium structures, with a repeat lattice distance that equals 2.5 times the vanadium lattice parameter along the c-axis. Our atomic resolution analysis of the interface will impact the mechanistic understanding of its interaction with interstitials and radiation-induced lattice defects, and consequently trigger the development of improved alloy structures with interfaces engineered for enhanced radiation tolerance. Graphical abstract: